How to create a nervous system aneurysm model in canines? ligation of the lingual artery is a simple and effective method - Liu, Zhengli; Yuan, Yuan; Jiang, Rui; Zhao, Boxiang; Gu, Jianping; He, Xu; Wang, Tao; Shi, Yadong; Li, Yinghao; Zhou, Yangyi; Fu, Guanqi; Chen, Liang; et al. (Frontiers in Physiology, 2023)
Background: The purpose of this research was to establish a safe, effective, and simple nervous system aneurysm model. This method could quickly and stably establish an exact canine tongue aneurysm model. This paper summarizes the technique and key points of the method. Methods: Under the condition of anesthesia by inhaling isoflurane with a mask, we punctured the femoral artery of the canine, and the tip of the catheter was placed in the common carotid artery for intracranial arteriography. The positions of the lingual artery, external carotid artery, and internal carotid artery were identified. Then, the skin near the mandible was cut according to the positioning and separated layer by layer until the bifurcation of the lingual artery and external carotid artery was exposed. The lingual artery were then sutured with 2-0 silk sutures approximately 3 mm from the external carotid/lingual artery bifurcation. The final angiographic review showed that the aneurysm model was successfully established. Results: The lingual artery aneurysm was successfully established in all 8 canines. All canines obtained a stable model of nervous system aneurysm and confirmed by DSA angiography. Conclusions: We have established a safe, effective, stable and simple method to establish a canine nervous system aneurysm model with controllable size. In addition, this method has the advantages of no arteriotomy, less trauma, constant anatomical location, and low risk of stroke.